1997
DOI: 10.1002/j.1552-4604.1997.tb04322.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Valproate on the Pharmacokinetics and Pharmacodynamics of Lorazepam

Abstract: The pharmacokinetic-pharmacodynamic interaction between valproate and lorazepam was evaluated in this randomized, double-blind, placebo-controlled crossover study. Sixteen healthy male volunteers enrolled in the study to receive either divalproex sodium (500 mg every 12 hours) or matching placebo for 12 days in the first period, and then to receive the other regimen for an identical second 12-day period. In both periods, lorazepam (1 mg every 12 hours) was administered on days 6 through 9 and on the morning of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 12 publications
1
26
0
Order By: Relevance
“…For example, CBZ and PHT, both potent inducers of CYP3A4, decrease the plasma concentration of midazolam (MDL), (129) whereas VPA increases the plasma concentration of lorazepam (LZP) by inhibiting UGT activity (130,131).…”
Section: Psychotropic Drugsmentioning
confidence: 99%
“…For example, CBZ and PHT, both potent inducers of CYP3A4, decrease the plasma concentration of midazolam (MDL), (129) whereas VPA increases the plasma concentration of lorazepam (LZP) by inhibiting UGT activity (130,131).…”
Section: Psychotropic Drugsmentioning
confidence: 99%
“…Four PK studies that compared the combination of valproic acid and lorazepam with lorazepam alone were identified. 9,[17][18][19] The data from those studies are summarized in Table 4.…”
Section: Discussionmentioning
confidence: 99%
“…18 All 4 studies showed that valproic acid cotreatment inhibited the metabolism of lorazepam, as indicated by an observed decrease in either lorazepam glucuronide formation clearance 17,18 or the metabolite AUC ratio. 9,19 With regard to elimination, a decrease in plasma clearance of lorazepam was observed in all 4 studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When used simultaneously with clonazepam, its clearance can increase by 14% while the clearance of valproate can decrease by 18% [29]. In cases of co-administration with lorazepam, the concentration time of lorazepam was found to increase by 20% and the maximum concentration by 8%; nevertheless, this had no significant impact on the therapeutic effect [30]. The other BDs do not react with valproic acid and may be used provided that clinical efficacy is maintained.…”
Section: Benzodiazepinesmentioning
confidence: 99%